Identifying the components of the administrative system employee empowerment model based on organizational intelligence and interpersonal relationships - fatemeh khoshhal; ali reza sargolzaie; zahra vazife (مدیریت و چشم انداز آموزش)
Abstract The purpose of this research is to identify the components of the model of empowerment of administrative system employees based on organizational intelligence and interpersonal relationships in the electricity industry of Sistan and Baluchistan Province. The statistical population includes 17 scientific experts and senior managers of electricity industry companies, who were selected through the purposeful and accessible sampling method. Semi-structured interviews were used to collect data and continued until reaching the theoretical saturation stage. To increase the scientific credibility of the results in the qualitative part, Merriam's method and percentage agreement coefficient were used. The data analysis was done using the inductive theme analysis method by Max QD software. The results of this stage were presented in the form of a model including antecedents, dimensions, adjusting factors, and consequences. The results of the present research show that the use of the organizational intelligence approach and interpersonal relationships is effective for empowering employees and has caused the conceptual development of this variable and the recognition of new dimensions of this phenomenon. Thus, the presented model can be a pioneer for the electricity industry in the effective implementation of these dimensions. Extended Abstract Introduction In the era of globalization and rapid advancement of technology, the most important asset of any organization is its human power, which plays a role more than other factors in maintaining and expanding the functional level and completing the mission of the organization (Tian et al., 2018). The prerequisite of a developed society is to have developed organizations, and developed organizations gain their strength and success through capable human resources. Empowerment makes employees feel more responsible for better performance in the organization (Greasley et al., 2008). Today, empowerment is considered as one of the useful tools for improving the quality of employees and increasing organizational effectiveness. Since empowerment is a strategy, its prerequisites must be met and the strategies and practical actions must be used for its implementation in the organization; therefore, paying attention to the capabilities of organizational intelligence and interpersonal relationships in the development of employee empowerment is considered vital. Intelligence is one of the undeniable requirements for the survival of organizations and represents the total knowledge that an organization takes from the environment in which it operates. Organizational intelligence is the best response to environmental challenges. Organizational intelligence enables organization employees to adapt to environmental changes and manage environmental complexity (Miidom, et al., 2022). The importance of communication and interpersonal relationships in organizational environments is undeniable; interpersonal relationships in the organization refer to different ways, strategies, and tools that employees use in their communication activities (Arora & Rangnekar, 2016). Interpersonal relationships in the organization help employees to share what they know and feel with each other, and is one of the most important factors affecting the performance of employees, which plays an important role in achieving goals (Kyongo, 2016). That is why in recent years, interpersonal relationships have received serious attention as a basic requirement for successful job performance from managers and organizational researchers (Damghanian et al., 2017). In this context, it is necessary to use its key components for superior performance in carrying out professional responsibilities. Theoretical foundations Empowerment Empowerment means designing a structure in such a way that people can achieve sufficient growth while controlling themselves to accept more responsibilities in the future (Mirmohammadi et al, 2016). Empowerment of human resources is a new motivational in-job approach that causes flourishing of talents and competencies of people by releasing the internal forces of employees (Shahravi, 2021). Organizational intelligence Albrecht considers organizational intelligence to be the capacity of an organization to utilize all its mental forces and concentrate these thoughts to perform tasks (Albrecht, 2003). Interpersonal relationships The importance of interpersonal communication and relationships in organizational environments is undeniable; so that it can be considered one of the vital factors for job performance and success. Interpersonal relationships are a process by which people's information and feelings are shared through verbal and Non-verbal messages and must be done effectively to ensure the achievement of organizational goals (Keyton et al, 2013). Research methodology The current research is applicable in terms of purpose, and qualitative in terms of method, in which semi-structured interviews were used to extract the research components and parameters. The investigation of the background of the current research showed that the nature of this issue has not been well explained. Therefore, the method of inductive theme analysis (theme analysis) has been considered as a qualitative research method. In this research, academic experts and senior electricity managers were interviewed in order to achieve the components of the employee empowerment model based on organizational intelligence and interpersonal relationships. The selection criteria of experts are theoretical mastery, practical experience, willingness to participate, and availability. The number of participating experts was 17. According to the previous agreement with them, their names have been avoided in the text of the article. The participants in the interviews were selected in a purposeful and available manner, and the process of interviews continued until the theoretical saturation was reached. To collect data from the interviews Semi-structured interviews were used. After the interviews were completed and theoretical saturation was reached, the data from 17 interviews were analyzed using MAXQDA software. Research findings In the qualitative part, the data obtained from the interview was analyzed with the help of inductive thematic analysis. The data analysis process was restarted with open coding. Open coding was first implemented in the content of all the interviews; after extracting the initial codes, the conceptually and content-wise shared codes were merged and formed the basic themes. Also, the basic concept shared themes were merged and formed the organizing themes. The results of this stage were presented in the form of a model including antecedents, dimensions, adjusting factors and consequences. Discussion The purpose of this research is to identify the components of the empowerment model of administrative system employees based on organizational intelligence and interpersonal relationships in the electricity industry of Sistan and Baluchistan province. Based on the findings of this study, 9 dimensions were identified for the dimensions of administrative system employee empowerment based on organizational intelligence and interpersonal relationships, including personal empowerment, attitudinal empowerment, cognitive empowerment, communication empowerment, managerial empowerment, organizational empowerment, social empowerment, knowledge/informational empowerment, and spiritual empowerment. This model has the dimension of comprehensiveness and hindrance and it has been able to include all native and specific aspects of organizational intelligence and interpersonal relationships that are effective in empowering employees, and there is no part of the model that is extra or not useful. Also, from the practical aspect, it is the answer to a real business problem. In general, it can be said that the use of the organizational intelligence approach and interpersonal relationships in empowering employees is effective and appropriate, and the model of this research has been able to provide a more realistic and comprehensive view and provide useful practical knowledge for the use of managers.